2005
DOI: 10.1007/s10517-006-0020-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Primary Allogenic Response by CD8+ Memory Cells

Abstract: Immune response to allogenic tumor cells is associated with the appearance of long-living CD8+ memory cells capable of rapid restimulation and lysis of tumor cells in case of repeated injection of these cells. In order to acquire the effector function, allorestricted memory cells need antigen restimulation for 2 days, which is a specific feature of central memory cell population. These cells can suppress proliferation of naive splenocytes in vitro. In mixed lymphocyte cultures containing memory cells, antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…To track changes in TCR repertoires during the primary and secondary immune responses, we exploited an experimental mouse model of induction of the immune response in C57BL/6 mice (of the H2-K b haplotype) to mastocytoma P815 (K d D d ) [18] . Due to differences in MHC class I molecules, P815 tumor cells elicit a strong CD8 + allogeneic response in these mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To track changes in TCR repertoires during the primary and secondary immune responses, we exploited an experimental mouse model of induction of the immune response in C57BL/6 mice (of the H2-K b haplotype) to mastocytoma P815 (K d D d ) [18] . Due to differences in MHC class I molecules, P815 tumor cells elicit a strong CD8 + allogeneic response in these mice.…”
Section: Methodsmentioning
confidence: 99%
“…Due to differences in MHC class I molecules, P815 tumor cells elicit a strong CD8 + allogeneic response in these mice. As previously described [18] , long-lived central memory cells are established in immunized C57BL/6 mice two months following in vivo P815 cell transplantation. Our recent study showed that the phenotypic characteristics of T cells (especially the expression of the CD44 molecule in mice) didn't necessarily correlate with their actual antigenic experience [19] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally, the suppression of naive T proliferation by secondary activated Tcmra was not surprising because this is in keeping with other reports that demonstrated both suppression of bystander Tnaive during secondary activation and suppression of primary allogenic response by CD8 + memory cells. Incidentally, this effect of Tnaive bystander suppression is also IL-10 dependent (36)(37)(38)(39). Another noteworthy observation is the CD161 expression in Tem, because more work may be necessary to ascertain the possibility of whether such chronically stimulated Tem are indeed precursors to the Th17 lineage (40).…”
Section: Discussionmentioning
confidence: 99%
“…To do this, we used the mixed lymphocyte reaction (MLR) of lymphocytes from animals immunized by allo geneic tumor cells as responder, and allogeneic spleno cytes, killed by severe heat shock (45°C, 1 h) as stimula tor cells. We have shown that this experimental system allows selective detection of proliferation of memory CD8 T cells specific to the immunizing MHC class I molecule and capable of recognizing its mutant forms [14,15]. This simple approach enabled us to obtain clones and T hybridomas of memory cells that in turn opened the way to molecular identification and cloning of their TCRs [16].…”
mentioning
confidence: 99%